Impact of Anemia on Quality of Life Among Patients on Dialysis with End-Stage Renal Failure - Omar, Rosnah; Kunjukunju, Annamma; Fariza, Nurul (Asian Journal of Public Health and Nursing, 2024)
Background: Reductions in quality of life among patients with End-Stage Renal Failure (ESRF) can be further compromised by anemia, which is a common complication of ESRF. This study evaluated the impact of anemia on the quality of life among dialysis patients with ESRF in a private dialysis center in Kuantan. Methods: The study used a cross-sectional design conducted on 113 ESRF patients at multiple dialysis centers in Kuantan. Demographic, socioeconomic, and disease status data were collected, and the Kidney Disease Quality of Life (KDQOL) short-version questionnaire was used to assess the patient's quality of life. Statistical analysis was performed using SPSS 26 to identify correlations among patient factors. Results: The study findings revealed that 46.4% have mild anemia, 38.4% have moderate anemia, and 16.2% have severe anemia.76% of respondents rated the quality of life as "Bad" and 6% as "Very Bad". Only 19% of respondents have rated the quality of life as "Normal." Conclusion: The findings suggest that anemia significantly affects the quality of life of patients with ESRF. These findings can help healthcare providers develop interventions to manage anemia and improve the quality of life of these patients. The study also emphasizes the importance of regular monitoring and management of anemia among patients with ESRF to ensure optimal health outcomes.